A REVIEW OF UNIVERSAL DESIGN ON ELDERY HOUSE DESIGNS DEVELOPMENT –CASE SOUTH KOREA- - Harsritanto, Bangun I R (MODUL, 2016)
The evolution toward Universal Design was began in the 1950s with a new attention to design for people withdisabilities. At the same era South Korea began their development after several wars. Recently some of researchs andprojects in South Korea which conducted on Universal Design concept are increasing in quantity and widening inmultidiciplinary areas to make a better living for people in South Korea.This study examined those researches andprojects to determine the progress of Universal Design principles application in South Korea in several periods andevaluated the result by the project’s purpose. This study is a review from several literatures related to universal designapplication in South Korea.The Review revealed that South Korea has published regulations, guidelines and law basedon universal design principles. South Korea has established universal design principles as fundamental basis indesigning and developing their elderly residential houses. Application of universal design influenced the knowledge ofdiversity for people especialy in disability and elderly. Universal design encourage people with diversity in ability, ages,gender to live together without barrier to access and use every facilities in their regions.